Criminal Liability of Love Scam Perpetrators in the Perspective of Positive Law and Islamic Criminal Law - Solihin, Riadus; Zuhri, Ahmad (IHSA Institute, 2024)
The criminal act of love scam is a form of fraud that has been transformed into the online realm. The fraud is the same as conventional fraud, but the difference is the place where the fraud occurs. Love scam cases occur because women who are often victims are lulled into love that is full of lies. This love scam case is very worrying because it blackmails the victim by loving them. The object of this research is focused on criminal liability for love scams from the perspective of positive law and Islamic criminal law. This research is empirical research, where researchers try and describe and analyze this practice with a normative approach, referring to the provisions of positive law and Islamic criminal law. Data collection by going directly into the field through interviews. Meanwhile, in analyzing the data, researchers used descriptive analysis. This research concludes that criminal liability for perpetrators of love scams is regulated in two statutory regulations, namely in Article 378 of the Criminal Code (KUHP) and Law Number 19 of 2016 concerning Information and Electronic Transactions. And accountability for perpetrators of fraud under the guise of romance according to Islamic criminal law is subject to ta'zir punishment and in its provisions depends on the judge's ijtihad